Oligomer formation of SARS-CoV-2 ORF8 through 73YIDI76 motifs regulates immune response and non-infusion antiviral interactions - Assadizadeh, Mohammad; Azimzadeh Irani, Maryam (Frontiers in Molecular Biosciences, 2023)
Introduction: Open Reading Frame 8 (ORF8) is a 121 amino acid length SARS-CoV-2 specific accessory protein that plays crucial roles in viral infectivity, and pathogenesis. Current SARS-CoV-2 treatments focus on spike or RNA-dependent RNA polymerase proteins. Hence, directing attention to ORF8 yields substantial benefits for innovative non-infusional therapeutics. Functional ORF8 is proposed to form oligomers via a crystallographic contact centered by 73YIDI76 motifs. Methods: Hence, the structure and atomistic interactions of trimeric and tetrameric ORF8 oligomeric forms were modeled by means of thorough molecular modeling and molecular dynamics simulations. Results: Results show that trimeric and tetrameric oligomers are stabilized by the interaction of β4-β5 (47-83) loops. 73YIDI76 motifs are involved in obtaining the oligomerization interfaces. It is shown that the tetramers which resemble a doughnut-like construction are the most stabilized oligomeric forms. Where four β4-β5 loops form the interfaces between two dimers. Each monomer links to two others through β4-β5 loops and a covalent Cys20-Cys20 bridge. Epitope mapping, binding site predictions, and solvent-accessible surface area analyses of different ORF8 forms show that the B-cell, MHC-I, and drug epitopes stay exposed in oligomeric forms. Discussion: Approving that the viral infectivity is expanded upon ORF8 oligomerization and the regions involved in oligomerization can be considered as therapeutic targets.